Disaster Journalism and Media Responsibility: Coverage of Flood Disasters in Lampung - Nasution, Nadya Amalia; Wahyuni, Sri; Frasetya, Vito (Jurnal Kajian Jurnalisme, 2025)
Local media in Lampung demonstrated varied disaster journalism implementation during the 2024 flood coverage. Despite possessing strengths in early warning systems and ethical reporting, weaknesses persisted: coverage limited to chronological events without in-depth analysis, inadequate preparedness of educational content, and weak post-disaster rehabilitation reporting. This study examines the implementation of disaster journalism principles in flood coverage by three major Lampung online media outlets: Lampungpost.co, Radarlampung.co.id, and Tribunlampung.co.id during 2024. Using a qualitative descriptive approach with a social responsibility theory framework, data were collected through content analysis of 72 news articles regarding flood (January to May 2024), in-depth interviews with editors-in-chief and coverage managers, and document review of coverage processes. The findings reveal suboptimal disaster journalism implementation across all disaster phases. The pre-disaster phase lacked comprehensive educational content. During disasters, though ethical standards were maintained, focus remained limited to chronological events. The post-disaster phase showed significant weaknesses in rehabilitation coverage and government accountability. The absence of specialized disaster journalism training emerged as a critical limiting factor. The study recommends specialist training programs, collaborative frameworks between media and disaster management agencies, and comprehensive coverage guidelines.